MTQ ; Antara Seni Membaca Alquran dan Politik Akomodasionis Pemerintah terhadap Umat Islam - Sri Handayana; Muhamad Rezi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2018)
MTQ is a manifestation of Islamic culture and is constantly evolving. MTQ is also one of the government policies related to Muslims and even seems to accommodate the interests of Muslims. The author believes that MTQ can be investigated from various aspects. If viewed from a religious perspective, MTQ is one way to improve spiritual life. If viewed from an economic standpoint, MTQ can support economic development through exhibitions or bazaars held in the main arena. Whereas if it is highlighted with the political glasses of MTQ, perhaps on the one hand the government is accommodating towards Muslims. This paper attempts to describe MTQ and its ins and outs, then also attempts to analyze MTQ as a form of aesthetic reception of the Qur'an and the political dimension of MTQ. The effort to express the Koran aesthetically has actually emerged since the time of the Prophet Muhammad. One of the most popular stories is about the Islamic story of Umar ibn Khattab after hearing the reading of several verses of the Qur'an by his younger sister named Fatimah with her husband named Sa'id bin Zayd. Therefore MTQ is an opportunity to develop the art of reading the Qur'an, and an event to foster awareness to read and study the Qur'an.